Pengaruh Persepsi Sosiologi Kritis, Kecerdasan dan Mentalitas Terhadap Pemahaman Pendidikan Akuntansi pada Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis - Basmal Mahbub Habibi; Abdul Wahid Mahsuni; Junaidi Junaidi (Universitas Islam Malang, 2023)
This study aims to find out the effect of the understanding of Accounting in Accounting student. The variable used to determine understanding of accounting education, critical sociology perception, intelligence and mentality. Based on the data obtained from University of Islam Malang, Merdeka University of Malang and University of Malang, there are 89 number of student that meet the criteria or quality as research sample. Moreover, the purposive sampling method was used to determine the sample with certain criteria and the analysis technique used wis multiple linier regression analysis with research data in the panel data. This result of the study showed that critical sociology perception as a significantly effect to understanding of accounting education. The second result, intelligence showed that has a significantly effect to understanding accounting education. While, the mentality scale showed that has no significant effect to understanding of accounting education. However, the effect of three variables simultaneously showed that critical sociology perception, intelligence, and mentality scaly simultaneously influences to understanding study of accounting education.Keywords: Understanding of accounting education, critical sociology perception, intelligence, mentality.